Intestinal necrosis and sigmoid colon obstruction due to bilateral strangulated femoral hernia in a male: a rare surgical and anatomic case report. Issue 11 (29th November 2021) - Zarokosta, Maria; Paraskevas, George; Chrysanthou, Chrysanthos; Piperos, Theodoros; Foutsitzi, Aikaterini; Nikas, Dimitris; Mariolis-Sapsakos, Theodoros
Abstract: Bilateral femoral hernia is a peculiar clinical condition, with female predominance, with only a few cases reported in the literature. There are only two cases of bilateral strangulated femoral hernias, and these occur solely in females. To our knowledge, in the present manuscript, a bilateral strangulated femoral hernia in a male patient is reported for the first time. A 68-year-old male proceeded to the emergency department of our institution with symptoms of bowel obstruction. Abdominal computed tomography, magnetic resonance imaging and subsequent emergency laparotomy revealed obstruction of the sigmoid colon and simultaneous necrosis of several loops of the small intestine due to bilateral strangulated femoral hernia. The operation was uneventful. Despite the scarcity of this clinical condition, surgeons' awareness is fundamental, in addition to deep knowledge of the pathology and the anatomy of femoral hernias, in order to diagnose and treat adequately strangulated and incarcerated femoral hernias.